FACTORS AFFECTING THE ABILITY OF SCIENCE PRE-SERVICE TEACHERS OF ELEMENTARY EDUCATION IN INDONESIA - Sumantri, Mohamad Syarif; Wibowo, Firmanul Catur (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
This study aims to obtain information on the effect of attitudes towards science, achievement motivation and learning activities on science learning outcomes. This research has been conducted in the elementary school teacher education institutions in Jakarta, Bogor and Tangerang District, Indonesia. In this study, 200 samples were randomly selected, and data was collected through a survey. The respondents were the students who took the science course. This study used quantitative approach, survey methods, and path analysis. Data were analyzed using descriptive analysis, analysis of the requirement test, and inferential analysis. The research findings indicate: 1) science learning outcomes are positively influenced directly by attitudes towards science, achievement motivation and learning activities, 2). learning activities are directly influenced positively by attitudes towards science and achievement motivation. on these findings, it can be concluded that the increase in science learning outcomes is influenced by attitudes towards science, achievement motivation and learning activities.